A wireless railway catenary structural monitoring system: Full-scale case study. (December 2016) - Nåvik, Petter; Rønnquist, Anders; Stichel, Sebastian
Highlights: Wireless sensor system used to sample accelerations of catenary systems under train passages. Sampled field data was successfully used to assess the dynamic behaviour. Analysis of the data show that the system is capable of monitoring relevant structural behaviour. The modal results can be used for updating numerical models. Abstract: Full-scale structural measurements of new and existing railway catenary systems are becoming increasingly important due to continually increasing train speeds and the resulting consequences. Higher speeds lead to increased loads and greater structural dynamic responses, necessitating that both static and dynamic regulations be fulfilled. Sampling directly on railway catenary sections is necessary to assess their structural behaviour. The results can both be analysed directly and be used for validating and/or improving numerical models, which in turn can be used to explore the structural response at higher speeds. This case study presents and explores a newly developed wireless sensor system that includes multiple sensors that can be mounted arbitrarily on any of the wires in a catenary system. All sensors synchronously sample accelerations and rotational velocities over a range of up to 1400 m. This paper shows the results of mounting the developed sensor system and sampling the data of an existing railway catenary section at the Hovin station in Norway. Sampling was performed from both self-excited tests and 140 scheduled train passages. The outputs have been analysed to show that the data can be used to successfully assess railway catenary structural response components.